Bioprospecção de isolados de leveduras e bactérias, provenientes da secreção oral de Diatraea saccharalis (Fabricius, 1794) (Lepidoptera: Crambidae) coletada em campo, antagônicos a Fusarium verticillioides (Nirenberg, 1976) e Colletotrichum falcatum (Went, 1893) - Silva, Larissa Chariel Domingos da (2016)
Insect symbionts may have unknown functions in the interaction between insect-plant and insect with microorganisms that co-inhabit the same space. The objective of this study was to investigate the antagonism potential of symbiont microbiota from oral secretion D. saccharalis collected in the field, against Fusarium verticillioides and Colletotrichum falcatum pathogens commonly found inside the cane. For this, 4° and 5° instar caterpillars were collected inside sugarcane varieties RB-835 054 and SP- 813 250, and brought to the lab inside the cane stalks. The microbiota of oral secretion was transferred to two selective media, NA (nutrient agar) for bacteria and DRBC (dicloran Rose Bengal Chloramphenicol) for yeast. Based on morphology and coloration of the colonies twenty colonies of bacteria and yeast were selected. Four culture media were tested in co-cultivation of F. verticillioides and C. falcatum versus bacteria or yeast isolates: PDA (potato, dextrose, agar), YEPD (yeast extract, peptone, dextrose), CCS (supplemented cane broth) and NA (Nutrient Agar). The most suitable culture medium for growth of most microorganisms was BDA. Antagonism potential of 82 bacterial isolates and 87 yeast isolates to C. falcatum and F. verticillioides was assessed using a visual scale of categories 1 to 4, with 4 being the maximum degree of antagonism. Isolates that allocated category greater than or equal to 2 were evaluated in co-culture with C. falcatum and F. verticillioides as the percentage of growth inhibition. It was possible to identify four isolates of bacteria which have the potential to inhibit growth of pathogens and 9 isolates with the same potential but with much lower percentages. These results demonstrate that some isolates of bacteria and yeast may influence the relationship between the bit-rot complex and sugarcane plant, may in future be used as a biological control of these pathogens or have some molecules of biotechnological interest extracted and purified.